Training on AI- and Computer-Based Hybrid Mathematics Learning Media with the Integration of Local Cultural Values at Training and Education Institutions - Rahmi Hayati; Eka Pandu Cynthia; Supiyandi Supiyandi; Irham Hidayat Shiddiq; Noor Vika Hizviani; Enda Beatrix Middlen Perangin-Angin (LKP KARYA PRIMA KURSUS, 2026)
The development of Artificial Intelligence (AI) technology and computer-based learning media requires educators to possess adaptive and innovative digital competencies. However, the utilization of AI technology in mathematics learning at Course and Training Institutions remains suboptimal due to educators’ limited ability to develop technology-based learning media and the lack of integration of local cultural values into the learning process. This community service activity was conducted at LKP KARYA PRIMA KURSUS, Medan, Indonesia, with the aim of improving educators’ competencies in designing AI- and computer-based mathematics learning media integrated with local cultural values through a hybrid training model. The implementation method employed a participatory approach consisting of needs analysis, training preparation, hybrid training implementation, mentoring, and program evaluation stages. The participants involved 25 educators from LKP KARYA PRIMA KURSUS. Data collection instruments included observation sheets, questionnaires, and competency tests. The results showed that participant attendance reached 96%, AI application usage skills reached 84%, learning media development skills reached 80%, and participant satisfaction reached 92%. In addition, post-test results increased by 78% compared to pre-training conditions. These findings indicate that the hybrid training implemented at LKP KARYA PRIMA KURSUS effectively enhanced educators’ digital competencies and supported the development of innovative mathematics learning integrated with local cultural values. The program also strengthened educators’ readiness to integrate AI technology into mathematics instruction, thereby contributing to the improvement of learning quality and digital transformation in non-formal education institutions.